Predictors of Mexican American Nursing Student Academic Success - (:unkn) unknown (My University, 2013)
The shortage of nurses in the United States has been an ongoing concern. The need to meet the overall demand for qualified nurses is compounded by the lack of minority representation in nursing. While there are disparities in the representation of all racial/ethnic groups in nursing the lack of Hispanic nurses is of special concern. Hispanic's in the United States, at 16 percent of the total population, constitutes the nation's largest racial/ethnic minority (U.S. Census 2010). Within the Hispanic population those of Mexican American ancestry account for 63 percent of the total population. To address the health needs of America's increasing Hispanic/Mexican American heritage population it is important that nurses are capable of providing culturally and linguistically appropriate care. To meet the need for Hispanic/Mexican American nurses, decrease potential health disparities related to culture, and wisely utilize resources it is important that Mexican American nursing students are academically successful. The purpose and design of this study was an initial exploration of predictors of Mexican American nursing student academic success. The theoretical framework used to guide the study were Tinto's (1975) model of student integration, Bandura's (1983) self-efficacy theory, and perceived social support (Zimet, Dahlem, Zimet, & Farley 1988, Rook & Doolye 1985, Norbeck & Tilden 1988; Malecki & Demaray 2002; Cohen & Wills 1985; Procidano & Heller 1983). The sample consisted of Mexican American (n=188) students enrolled in the first or second semester of nursing clinical coursework at either an associate (n=2) or bachelor (n=1) degree nursing program located in south Texas. Data was collected through face to face administration of three research instruments and a demographic survey. Direct binary logistic regression was used to examine the contribution select contextual and socio-demographic attributes, student integration, academic self-efficacy, and perceived social support had on predicting academic success. The analysis of data indicated that program type, bachelor degree of nursing, contributed to predicting success (ρ=.004; Exp(B)=4.988). The results of the investigation broaden the knowledge related to predictors of Mexican American nursing student academic success. In particular the importance of baccalaureate education for primary preparation in nursing for Mexican American students was identified.
Keywords: Academic; Education; Student